2016
DOI: 10.1007/s10068-016-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and identification of proteins interfering with enzyme-linked immunosorbent assay of antibiotics in fish matrix

Abstract: The interaction between some proteins and immune globulin has been confirmed as an important source of matrix interference with the immunoassay of fishery products, but detailed biochemical properties of these proteins have not been indicated. Two interference-inducing proteins (42 and 36 kD) in flounder were isolated, characterized, and identified. Their influences on the immunoassay of norfloxacin were confirmed by western blotting and enzyme-linked immunosorbent assay. The pI value and pH stability of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Chlorophyll is unstable and easy to decompose under acidic conditions, 31 therefore a new idea based on the pretreatment with acids was suggested here. Among various acids, 5‐sulfosalicylic acid has demonstrated excellent ability to eliminate matrix proteins with little effect on the ELISA and other immunoassays 24,32,33 . Considering the excellent stability of procymidone under acidic conditions, in principle 5‐sulfosalicylic acid would not react with procymidone or lead to its breakdown 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll is unstable and easy to decompose under acidic conditions, 31 therefore a new idea based on the pretreatment with acids was suggested here. Among various acids, 5‐sulfosalicylic acid has demonstrated excellent ability to eliminate matrix proteins with little effect on the ELISA and other immunoassays 24,32,33 . Considering the excellent stability of procymidone under acidic conditions, in principle 5‐sulfosalicylic acid would not react with procymidone or lead to its breakdown 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Among various acids, 5-sulfosalicylic acid has demonstrated excellent ability to eliminate matrix proteins with little effect on the ELISA and other immunoassays. 24,32,33 Considering the excellent stability of procymidone under acidic conditions, in principle 5-sulfosalicylic acid would not react with procymidone or lead to its breakdown. 34 These proposals were confirmed well by the following experiments.…”
Section: Matrix Effect Analysismentioning
confidence: 99%
“…Previous researches have demonstrated that the matrix components, notably proteins in sh and other animal-derived foods, might create signi cant matrix effects in immunoassays since the accuracy of immunoassays can be impacted by sample matrix (Wang et al 2016;Wang et al 2013;Xu et al 2012). As can be seen from Fig.…”
Section: Analysis Of 2e6-sumo In Sh Matrixmentioning
confidence: 99%